2022
DOI: 10.1021/acs.est.2c04727
|View full text |Cite
|
Sign up to set email alerts
|

Paper Device Combining CRISPR/Cas12a and Reverse-Transcription Loop-Mediated Isothermal Amplification for SARS-CoV-2 Detection in Wastewater

Abstract: Wastewater-based surveillance of the COVID-19 pandemic holds great promise; however, a point-of-use detection method for SARS-CoV-2 in wastewater is lacking. Here, a portable paper device based on CRISPR/Cas12a and reverse-transcription loop-mediated isothermal amplification (RT-LAMP) with excellent sensitivity and specificity was developed for SARS-CoV-2 detection in wastewater. Three primer sets of RT-LAMP and guide RNAs (gRNAs) that could lead Cas12a to recognize target genes via base pairing were used to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…Ramírez-Chavarría et al combined an electrochemical sensor with RT-LAMP for the detection of SARS-CoV-2 in wastewater samples and showed that the sensor was able to specifically quantify RT-LAMP amplicons at a level below 2.5 × 10 –6 ng/μL, showing high reproducibility (Ramírez-Chavarría et al 2022 ). Cao et al developed a portable paper-based device based on CRISPR/Cas12a and reverse transcription LAMP for semi-quantitative analysis of SARS-CoV-2 in wastewater, and the device achieved semi-quantitative analysis from 0 to 310 copies/mL with good sensitivity and specificity, which is a method that could be a promising approach for wastewater monitoring (Cao et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ramírez-Chavarría et al combined an electrochemical sensor with RT-LAMP for the detection of SARS-CoV-2 in wastewater samples and showed that the sensor was able to specifically quantify RT-LAMP amplicons at a level below 2.5 × 10 –6 ng/μL, showing high reproducibility (Ramírez-Chavarría et al 2022 ). Cao et al developed a portable paper-based device based on CRISPR/Cas12a and reverse transcription LAMP for semi-quantitative analysis of SARS-CoV-2 in wastewater, and the device achieved semi-quantitative analysis from 0 to 310 copies/mL with good sensitivity and specificity, which is a method that could be a promising approach for wastewater monitoring (Cao et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…This is the first report of a LAMP-CRISPR detection system on paper. Previously all LAMP-CRISPR reactions have been carried out in tubes or in combinations of tubes plus lateral flow devices [8], [30].…”
Section: Sensitivity Studiesmentioning
confidence: 99%
“…Many µPADs and µTAS have been developed to detect pathogens from a wide range of matrices, including food sources, wastewater, drinking water, and human serum and blood amongst others, and have been used for a variety of applications such as food and drinking water quality control, environmental monitoring, and clinical analysis. [46][47][48][49][50][51][52] However, the detection mechanism typically employed by these devices is often based on DNA amplification or protein detection that are not suitable biomarkers for cell viability, and therefore cannot be used for live pathogen sensing.…”
Section: Microfluidic Platforms For Detection Of Live Microorganismsmentioning
confidence: 99%